Chemical synthesis of new histone deacetylase inhibitors and their evaluation as inducers of recombinant protein production in plants - Rebelo, Bárbara Almeida (2020)
"Transgenic plants offer several advantages for the production of recombinant proteins with pharmaceutical value. Moreover, plant suspension cell cultures combine the benefits of plants with the advantages of recombinant protein production by microbial cell cultures. Histones are proteins that are essential in gene expression control through several modifications like acetylation, phosphorylation and methylation. Histone acetyltransferases and histone deacetylases regulate the expression levels via acetylation and deacetylation of lysine residues in histones. Therefore, histone acetylation is associated with an increase in transcription levels, resulting in higher protein production levels. Inhibitors of these HDACs have been associated with the treatment of prostate and lymphoma cancer, reactivation of latent HIV cells and they also behave as small molecular enhancers for recombinant protein production.(...)"